2023
DOI: 10.2147/tcrm.s405507
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Herbs as Complementary and Alternative Therapy in Recovery and Clinical Outcome Among People with COVID-19: A Systematic Review, Meta-Analysis, and Meta-Regression

Abstract: Background The COVID-19 pandemic continues, and this condition has caused many cases in various countries around the world, resulting in more than 6 million deaths worldwide. Herbal medicines can act as immunomodulators, anti-inflammatories, antioxidants, antimicrobials, and others depending on the type and content of the herbs used. Previous studies have shown that several types of herbs, such as Echinacea purpurea, Curcumin or Turmeric, Nigella sativa, and Zingiber officinale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Several case studies have already been conducted to assess the effectiveness of phytochemicals as anti-SARS-CoV-2 agents in human subjects [ 113 ]. A systematic review and meta-analysis have shown that in the realm of COVID-19 management, herbal medicine presents itself as a promising adjuvant therapy with substantial potential [ 118 ]. Furthermore, available evidence suggests that Traditional Chinese Medicine medications demonstrate efficacy in alleviating symptoms among patients with COVID-19 [ 110 ].…”
Section: Background and Key Issues Of The Covid-19 Pandemic In Indonesiamentioning
confidence: 99%
“…Several case studies have already been conducted to assess the effectiveness of phytochemicals as anti-SARS-CoV-2 agents in human subjects [ 113 ]. A systematic review and meta-analysis have shown that in the realm of COVID-19 management, herbal medicine presents itself as a promising adjuvant therapy with substantial potential [ 118 ]. Furthermore, available evidence suggests that Traditional Chinese Medicine medications demonstrate efficacy in alleviating symptoms among patients with COVID-19 [ 110 ].…”
Section: Background and Key Issues Of The Covid-19 Pandemic In Indonesiamentioning
confidence: 99%
“…Herbal medicines, with their long history of use in traditional medicine, offer the potential to contribute to symptom relief, accelerate recovery, and strengthen the immune system. While no herbal preparation has yet been consistently shown to be effective in treating COVID-19, recent studies have shown some promising candidates as potential adjunctive or alternative therapies ( Al-kuraishy et al, 2022 ; Komariah et al, 2023 ; Kumar et al, 2023 ; Onyeaghala et al, 2023 ). This medicine has a long history across different cultures, and some plants have been recognized to possess antiviral, anti-inflammatory, and immunomodulatory properties relevant in the context of viral infections ( Nugraha et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%